(untitled) (Journal of The Colloquium for Information Systems Security Education, 2017)
With the fast development of Cyber-Physical Systems (CPS), security in these special application environments starts to attract more and more efforts. In this project, we form a team of researchers in information security, manufacturing, mechanical engineering, and education to jointly design a remotely accessible experiment platform for security education in advanced manufacturing systems (AMS). Students can reserve hardware equipment remotely and control it through a dynamically created virtual machine. Multiple types of hardware equipment, including PLC/MyRIO controlled elevator simulator, PLC/MyRIO controlled golf ball gripper, and a robotic arm, have been connected to the platform. Students can remotely operate on these machines and see their movements through high definition cameras. Course modules and experiments for security education in AMS have been designed upon the platform. These materials have been adopted by one undergraduate level mechanical engineering course. More than 130 hours of hands-on exercises have been conducted by students on this platform.